2021
DOI: 10.1039/d1dt03430h
|View full text |Cite
|
Sign up to set email alerts
|

From ferrocene to 1,2,3,4,5-pentafluoroferrocene: halogen effect on the properties of metallocene

Abstract: Impact of successive fluorinations onto redox, spectroscopic and NMR properties of ferrocene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 64 publications
3
10
0
Order By: Relevance
“…The comparison of these results with less brominated metallocenes (FeC 10 BrH 9 , E 1/2 = 0.110 V vs FeCp 2 0/+ ; see Table 1) shows that the oxidation potentials continuously increase with the level of bromination. This finding is consistent with the results for polyfluorinated FeC 10 F n H 10−n (n = 0, 1, 2, 3, 4, 5) 30 and polychlorinated metallocenes FeC 10 H 10−n Cl n (n = 1, 2, 5, 10). 24 This correlation was found to be linear for ferrocenes bearing the lighter halogens atoms (F, Cl) but not for brominated ferrocenes (this work).…”
Section: ■ Results and Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The comparison of these results with less brominated metallocenes (FeC 10 BrH 9 , E 1/2 = 0.110 V vs FeCp 2 0/+ ; see Table 1) shows that the oxidation potentials continuously increase with the level of bromination. This finding is consistent with the results for polyfluorinated FeC 10 F n H 10−n (n = 0, 1, 2, 3, 4, 5) 30 and polychlorinated metallocenes FeC 10 H 10−n Cl n (n = 1, 2, 5, 10). 24 This correlation was found to be linear for ferrocenes bearing the lighter halogens atoms (F, Cl) but not for brominated ferrocenes (this work).…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…While for mono- and disubstituted ferrocenes these correlations fit quite well (Figure ), the discrepancies become most visible at high halogenation levels. This is consistent with the results of Erb and co-workers, who showed that in the case of (poly)­halogenated ferrocenes the correlation between the redox potentials and R falls into distinct groups depending on the substitutional pattern but is nonlinear over all investigated metallocenes . Therefore, the explanation cannot be restricted to Hammett constants but should consider, as discussed by Erb and Inkpen previously, orbital reordering, changes in hybridization and frontier orbital composition, electrostatic repulsion between metal and Cp ring orbitals, and through-space interactions between the iron center and halogen atoms. , …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Indeed, many other factors such as orbitals ordering, changes in hybridization and frontier orbital composition, through-space interaction between the metal and the substituents as well as electrostatic repulsion between the metal and the Cp ring orbitals need to be considered. 147,151,154 Therefore, a better understanding of the substituent effect on the redox potential of a hetero polysubstituted ferrocene would require a dedicated study, which falls out the scope of this work.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%